Penerapan Model Cooperative Problem Solving untuk Meningkatkan Kerjasama Tim pada Pembelajaran IPS - Asep Wibowo; Siti Wahidah Hayati; Sundari Sundari; Sukarmi Sukarmi; Rustam Widaryanto; Muslimah Muslimah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The purpose of this study is to describe the steps, advantages, and disadvantages of implementing the Cooperative Problem Solving learning model in social studies lessons at Madrasah Tsanawiyah Negeri 4 Klaten Regency and Madrasah Tsanawiyah Negeri 5 Karanganyar. This study used a qualitative approach. The subjects of this study were teachers. Data collection techniques included interviews, observation, and documentation. The results of this study are as follows: 1) The steps of the Cooperative Problem Solving model include: the teacher divides students into groups of 3-4 students, the teacher explains the learning procedures, clarifies the problem, elicits opinions, evaluates and selects, and implements; 2) The advantages of the Cooperative Problem Solving model are that it makes education in school relevant to real life, helps students develop the habit of addressing problems in real life, fosters creative and comprehensive thinking processes in students, trains students to identify and conduct investigations, and provides students with opportunities to apply their knowledge in real-world contexts; 3) The disadvantages of the Cooperative Problem Solving model are that when students lack interest and do not believe that the problems being studied can be solved, they may become reluctant to try. Changing students' learning habits from passively listening to and receiving information from the teacher to actively thinking and solving problems on their own or in groups can be challenging, especially when it requires accessing various learning resources. The teaching and learning process using this method often requires a significant amount of time.